Exploración del efecto que produce el óxido de calcio vía drench en el cultivo de la papa, Comunidad de El Capulí. Parroquia El Carmelo, Cantón Tulcán, Provincia del Carchi - Quiranza Taticuan, Rolando Gustavo (2018)
SUMMARY Carchi was the first province of Ecuador in the potato production. However, in recent years its productivity has been low, affecting the economy of the families of the province. The present work is an exploratory document about the use of calcium oxide via drench. Six chapters have been developed: introduction, theoretical framework, characterization of the study area, results, conclusions and recommendations, bibliography and annexes. In each chapter you can find information about the importance of calcium, materials, methods, conclusions and recommendations. It is also shown analysis conducted in different assessments done during the experimental part. The aim of this proposal is to increase productivity and provide a better nutrition for the soil and the plant. With the use of calcium oxide, it was possible to have more number of stems, more height, root increase, greater emission of stolons and a greater weight of the root. Factors that helped that, in the treated plot, since the plant had two months fifteen days presented a curd of all the stolons emitted factor that is not very common to observe in the cultivation of the potato since usually the stolons begin to fill during the three months and a half and four months. Another interesting factor of the contribution of calcium was the evaluation of the weight of the root, since this is the basis for a better production, it could be appreciated that it had a balance between the root and the foliage (for a large plant a good root). All the elements that were measured and weighed are factors that indicate that if we have a good phytosanitary management and applications of calcium oxide, an increase in productivity and greater profitability for the farmer will be obtained.